2017
DOI: 10.1002/acr.22976
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide Trends in Hospitalizations and In‐Hospital Mortality in Granulomatosis With Polyangiitis (Wegener's)

Abstract: Background Granulomatosis with polyangiitis (GPA) is a type of ANCA-associated vasculitis associated with severe end-organ damage and treatment-related complications that often lead to hospitalization and death. Nationwide trends in hospitalizations and in-hospital mortality over the past two decades are unknown and were evaluated in this study. Methods Using the National Inpatient Sample (NIS), the largest all-payer inpatient database in the US, the trends in hospitalizations with a discharge diagnosis of G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 15 publications
1
23
2
Order By: Relevance
“…Interestingly, in our cohort, the survival rate for those with EGPA and those with MPA continued to decrease during the 10 years after diagnosis, in contrast to that in previous reports, in which higher mortality in AAV was attributed to the first year after diagnosis . This finding may be a reflection of the modern immunosuppressive strategies being utilized for AAV , leading to remission in more than 90% of cases and, thus, improved survival in the first year, although survivorship in EGPA and MPA is overall still lower than that in GPA.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…Interestingly, in our cohort, the survival rate for those with EGPA and those with MPA continued to decrease during the 10 years after diagnosis, in contrast to that in previous reports, in which higher mortality in AAV was attributed to the first year after diagnosis . This finding may be a reflection of the modern immunosuppressive strategies being utilized for AAV , leading to remission in more than 90% of cases and, thus, improved survival in the first year, although survivorship in EGPA and MPA is overall still lower than that in GPA.…”
Section: Discussioncontrasting
confidence: 88%
“…Surprisingly, we observed that GPA‐related mortality was no longer increased when compared to the mortality rate in the general population . Reasons for this observation of improved survivorship in those with GPA are uncertain, but may have been influenced by improved case identification, as was shown by the increased incidence of GPA, and likely could have been influenced by the close and consistent multispecialty follow‐up care provided in a tertiary care center once the diagnosis was established.…”
Section: Discussionmentioning
confidence: 62%
“…We know that cardiac and non‐cardiac vascular disease is significantly more likely in the presence of extra articular RA . GPA is also associated with a risk of mortality, although more recent evidence shows that despite hospitalizations increasing for this condition, mortality has significantly reduced over the last 15 to 20 years, presumably due to improved immunosuppressive therapy . Mortality linked to RA has also significantly decreased over the last decade .…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study of GPA patients in an all-payer U.S. inpatient database (National Inpatient Sample) reported that infections (particularly respiratory tract infections) were the most frequent reason for hospitalization (25%) and also a primary contributor to death (16.4% of all in-hospital mortality cases)(41). In our study, pediatric and working-age adult GPA cohorts had comparable high rates of severe infections, whereas the hospitalization rate was higher in pediatric GPA patients.…”
Section: Discussionmentioning
confidence: 99%